The role of neuroinflammation and amyloid in cognitive impairment in an APP/PS1 transgenic mouse model of Alzheimer's disease. (12th February 2017) - Zhu, Shenghua; Wang, Junhui; Zhang, Yanbo; He, Jue; Kong, Jiming; Wang, Jun‐Feng; Li, Xin‐Min
Summary: Aims: Both amyloid deposition and neuroinflammation appear in the early course of Alzheimer's disease (AD). However, the progression of neuroinflammation and its relationship with amyloid deposition and behavioral changes have not been fully elucidated. A better understanding the role of neuroinflammation in AD might extend our current knowledge to therapeutic intervention possibilities. Methods: This study systematically characterized changes in behavioral abnormalities in APP/PS1 transgenic mice. Brain pathology measures were performed in post‐mortem brain tissues of mice from 2 to 22 months. Results: APP/PS1 mice exhibited significant memory deficits from 5 months old, which were aggravated at the later stage of life. However, the degree of memory impairments reached a plateau at 12 months. An early appearance of amyloid plaques was at 3 months with a linear increase throughout the disease course. CD11b‐positive microglia and glial fibrillary acidic protein‐(GFAP) positive astrocytes were first detected at 3 months with a close association with amyloid plaques. Yet, the rate of changes in glial activation slowed down from 12 months despite the steady increase in Aβ. Conclusion: These findings provided evidence that neuroinflammation might be involved in the development and progression of cognitive deficits in APP/PS1 mice, suggesting novel intervention and prevention strategies for AD.